2021
DOI: 10.1161/circ.144.suppl_1.11221
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 11221: Counseling in the Time of COVID - Prenatal Diagnosis of Congenital Heart Disease During a Pandemic

Abstract: Introduction: Comprehensive prenatal care of congenital heart disease (CHD) relies on a multi-disciplinary approach that includes timely prenatal counseling and individualized care plans for the pregnancy, delivery and neonatal period. With the COVID-19 pandemic our fetal therapy clinic (FTC) approach to patient care was altered to accommodate restrictions, including the use of telehealth visits. We investigated whether counseling and access to care for fetal patients with CHD was negatively impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…While we had anticipated that such conditions would impact the ability of patients to receive ultrasound examinations and attend echocardiography referral appointments, leading to decreased quality of prenatal care and missed fetal cardiac screening opportunities, we postulate that this continued uptrend in prenatal diagnosis rates may have been augmented by successful COVID-19 accommodations within obstetric care as well as more comprehensive screening recommendations by multiple society guidelines. Several recent studies of prenatal care during the pandemic have suggested equal or even improved prenatal care utilization, including increased rates of initiation of prenatal care in the first trimester, unchanged numbers of total prenatal care visits, and equal-to-increased number of dating and anatomy ultrasound examinations [ 18 20 ]. One preliminary study that examined prenatal diagnosis of CHD at a single-center fetal therapy clinic that had implemented increased use of telehealth specifically found that patients had a similar gestational age at initial diagnosis of CHD, an earlier gestational age at referral and first visit, and longer pediatric cardiology counseling [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While we had anticipated that such conditions would impact the ability of patients to receive ultrasound examinations and attend echocardiography referral appointments, leading to decreased quality of prenatal care and missed fetal cardiac screening opportunities, we postulate that this continued uptrend in prenatal diagnosis rates may have been augmented by successful COVID-19 accommodations within obstetric care as well as more comprehensive screening recommendations by multiple society guidelines. Several recent studies of prenatal care during the pandemic have suggested equal or even improved prenatal care utilization, including increased rates of initiation of prenatal care in the first trimester, unchanged numbers of total prenatal care visits, and equal-to-increased number of dating and anatomy ultrasound examinations [ 18 20 ]. One preliminary study that examined prenatal diagnosis of CHD at a single-center fetal therapy clinic that had implemented increased use of telehealth specifically found that patients had a similar gestational age at initial diagnosis of CHD, an earlier gestational age at referral and first visit, and longer pediatric cardiology counseling [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies of prenatal care during the pandemic have suggested equal or even improved prenatal care utilization, including increased rates of initiation of prenatal care in the first trimester, unchanged numbers of total prenatal care visits, and equal-to-increased number of dating and anatomy ultrasound examinations [ 18 20 ]. One preliminary study that examined prenatal diagnosis of CHD at a single-center fetal therapy clinic that had implemented increased use of telehealth specifically found that patients had a similar gestational age at initial diagnosis of CHD, an earlier gestational age at referral and first visit, and longer pediatric cardiology counseling [ 20 ]. This was postulated to be due to the ability for patients to develop more comprehensive and individualized care plans with their care team via the flexibility of telemedicine appointments.…”
Section: Discussionmentioning
confidence: 99%